2013
DOI: 10.1155/2013/689827
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cell in Stroke: A New Paradigm for Immune Regulation

Abstract: Stroke is a common, debilitating trauma that has an incompletely elucidated pathophysiology and lacks an effective therapy. FoxP3+CD25+CD4+ regulatory T cells (Tregs) suppress a variety of normal physiological and pathological immune responses via several pathways, such as inhibitory cytokine secretion, direct cytolysis induction, and antigen-presenting cell functional modulation. FoxP3+CD25+CD4+ Tregs are involved in a variety of central nervous system diseases and injuries, including axonal injury, neurodege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 97 publications
0
34
0
1
Order By: Relevance
“…To investigate the role of T cells in TLE, Zhiguo et al used gene deficit mice to establish epileptic model; as a result: CD4/CD8 (-/-) mice showed the mildest seizure, CD8 (-/-) , wild-type mice displayed intermediate response, and CD4 (-/-) mice presented much more severe clinical features and 100 % early mortality. Histopathological detection in this study revealed the fewest pathological changes in CD4/CD8 (-/-) mice 7 days after KA-infusion [43]. Besides, Deprez's [55] and Zattoni's [7] studies also showed advanced spontaneous recurrent seizures (SRS) onset and delayed hippocampal destruction by neutrophils in RAG1-KO mice, indicating a neuroprotective role of T cells infiltrated in the epileptic focus.…”
Section: T Cellsmentioning
confidence: 51%
See 1 more Smart Citation
“…To investigate the role of T cells in TLE, Zhiguo et al used gene deficit mice to establish epileptic model; as a result: CD4/CD8 (-/-) mice showed the mildest seizure, CD8 (-/-) , wild-type mice displayed intermediate response, and CD4 (-/-) mice presented much more severe clinical features and 100 % early mortality. Histopathological detection in this study revealed the fewest pathological changes in CD4/CD8 (-/-) mice 7 days after KA-infusion [43]. Besides, Deprez's [55] and Zattoni's [7] studies also showed advanced spontaneous recurrent seizures (SRS) onset and delayed hippocampal destruction by neutrophils in RAG1-KO mice, indicating a neuroprotective role of T cells infiltrated in the epileptic focus.…”
Section: T Cellsmentioning
confidence: 51%
“…Regulatory T cell (Treg) is an innate immunomodulator involved in various CNDs, including stroke, axonal injury, and neurodegenerative disease [43]. In vitro and in vivo studies have indicated that Tregs can suppress the production of peripheral neutrophil-derived matrix metalloprotease (MMP-9), which alleviates proteolytic damage of BBB [44].…”
Section: Count Change Of Peripheral Cells After Epileptic Seizurementioning
confidence: 99%
“…When these subgroups are compared with the control group there was no significant difference. Chen et al, 2013). But results from experimental animal models of stroke suggest that Tregs can traffic to the site of the stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Adoptive transfer of Treg cells led to reduction of volume of ischaemia in experimental stroke (Brea et al, 2014). However, the role of Treg cells in recovery from stroke may be different at different time points after stroke (Chen et al, 2013;Kleinschnitz et al, 2013;Xu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Обладая супрессорной активностью, Тreg через модуля-цию воспалительного процесса могут защищать ткани мозга от ишемического повреждения. Так, Тreg секретируют противовоспалительные цито-кины (TGF-β, IL-10), подавляющие системное и локальное воспаление; ингибируют выработку металлопротеиназы-9, предотвращая нарушения гематоэнцефалического барьера; ингибируют ак-тивность Т-клеток в мозговой ткани и на пери-ферии; подавляют активацию микроглии [18,68]. Усиление активности Тreg с помощью ингибито-ра гистоновой диацетилазы приводит к сокраще-нию размеров поражения мозговой ткани [69].…”
Section: адаптивный иммунный ответunclassified